Rapid progression of subcutaneous glioblastoma: A case report and literature review - Wang, Fang; Dong, Jiawei; Zhang, Jiheng; Zhao, Hongtao; Wang, Nan; Jin, Jiaqi; Yan, Xiuwei; Gao, Xin; Liu, Han; Hu, Shaoshan (Frontiers in Oncology, 2023)
Extra-neural spread of Glioblastoma (GBM) is extremely rare. We report a case of postoperative intracranial GBM spreading to the subcutaneous tissue via the channel of craniotomy defect in a 73-year-old female. Radiological images and histopathology indicate the tumor microenvironment of the subcutaneous tumor is clearly different from the intracranial tumor. We also model the invasion of GBM cells through the dura-skull defect in mouse. The retrospective analysis of GBM with scalp metastases suggest that craniectomy is a direct cause of subcutaneous metastasis in patients with GBM. Imaging examinations of other sites for systemic screening is also recommended to look for metastases outside the brain when GBM invades or metastasis to scalp.